Proyecto de inversión para la creación de una empresa de servicios de hospedaje en cabañas ecológicas para la Parroquia Valladolid, Cantón Palanda Provincia de Zamora Chinchipe - Patiño Rivera, Leidy Elizabeth (2016)
The present investment project is focused in the implementation of some ecological cabins for the Parish of Valladolid in the Canton Palanda, County of Zamora Chinchipe. The general objective of the present study is to contribute to the development tourist echo of Valladolid and in yes to foment employment sources and mainly to contribute to the emprendimiento in the whole county through the implementation of ecological cabins with the purpose that our possible clients have the direct contact to the nature, the same one that for an effective execution and consolidation, it has been traced the specific following objectives. Firstly to develop a market study that allows to determine the economic characteristic partner of the tourists to obtain the offer and demand of the project, as second objective to carry out the technical study where it will be located the company, the macro and micro localization and in turn the whole necessary infrastructure that the cabins require for all the areas of service highlighting as main service to the lodging; the capacity installs it was calculated according to the number of beds that counts the cabins this multiplied by the number of tourists that visits the place a year manifesting that the company will cover 19,53% of these tourists. The third objective is focused to execute administrative alternatives of organization, manuals, flowcharts, human resource and of legal constitution that 5 you/they adapt to the requirements of the project in which consists the requirements to constitute it in legal. As last objective he/she thought about, to "Carry out the economic-financial study to determine the feasibility that the investment generated, with the application of necessary indicators and chords to the situation."where was obtained that one needs an investment of $266,412.17 as well as when applying financial indicators of evaluation it was obtained a they GO positive, the relationship benefit-cost of 2,58, TIR of 52,30%, and a sensibility of 72,71% in increment in costs and 16,95% in decrease in revenues. To achieve these objectives it was used methods like: the scientist, deductive, inductive, analytic, mathematical, synthetic, and technical of investigation like: it interviews, observation, bibliographical gathering, what I facilitate an orderly and truthful development of the different phases of the investment project, since allowed to pick up and to analyze data that threw the applied surveys. Finally he/she was carried out the conclusions and agreement recommendations with the results obtained in the elaboration of the project; you concluded that the project is focused to the success, it should take advantage of it to him offering services of quality combined with a good attention and an atmosphere pleasant chord to the different necessities of the clients for this way to maintain the client's fidelity, additionally this work was supported of the bibliography and annexes that it contemplates the investigation.